Mathematical development in Williams syndrome: A systematic review. (May 2020) - Van Herwegen, Jo; Simms, Victoria
Highlights: This systematic review identified only 27 studies that have examined mathematical abilities in Williams syndrome (WS). The majority of the studies reported that mathematical abilities are delayed in WS and are likely to follow an atypical developmental pathway. There is a lack of information on the cognitive mechanisms that underpin mathematical development in WS, leading to a lack of evidence-based interventions or changes to educational practice. Abstract: Background: The current systematic review is the first to systematically explore and synthesis research to date on mathematical abilities in Williams syndrome (WS), a rare genetic disorder that results in an uneven cognitive profile. As mathematical development is complex and relies on both domain-specific and domain-general abilities, it is currently not clear what mathematical abilities have been examined in WS and also what the current gaps in this research area are. Methods and procedures: A total of 27 studies across 22 publications were identified through a systematic review search process. Results: Overall, all mathematical abilities, except for simple counting and subitizing abilities, were reported to be impaired but in line with overall mental-age abilities. However, the literature to date has not established the underlying causes of these mathematical difficulties in WS. Some studies suggested that mathematical abilities in WS follow an atypical developmental pathway with a greater reliance on verbal abilities than in typical development but coupled with impaired understanding of counting and knowledge of the number system more broadly. However, most included studies used different assessments of mathematical skills and there is a lack of studies that have examined more than one particular aspect of mathematical development within the same study. In addition, studies have often included large age ranges and small participant samples, despite the known large individual variability in WS. Conclusion: Although we know mathematical abilities in WS are impaired, this area is under-researched and there is a lack of longitudinal studies that provide insight into the cognitive mechanisms that underpin mathematical development in WS. Therefore, there is a lack of an evidence-base to inform interventions or educational practice.